1996
DOI: 10.1016/s0092-8674(00)81824-3
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of an IHF-DNA Complex: A Protein-Induced DNA U-Turn

Abstract: Integration host factor (IHF) is a small heterodimeric protein that specifically binds to DNA and functions as an architectural factor in many cellular processes in prokaryotes. Here, we report the crystal structure of IHF complexed with 35 bp of DNA. The DNA is wrapped around the protein and bent by >160 degrees, thus reversing the direction of the helix axis within a very short distance. Much of the bending occurs at two large kinks where the base stacking is interrupted by intercalation of a proline residue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

32
908
0
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 781 publications
(941 citation statements)
references
References 56 publications
32
908
0
1
Order By: Relevance
“…Structures of HMGB/DNA complexes suggest that induced flexibility would likely be anisotropic [14;16]. HMGB proteins share some features with bacterial IHF [43] and X-ray structures of complexes of the similar HU protein with DNA suggest that a range of induced DNA bend angles are possible [44]. Results from atomic force microscopy for DNA/ HU complexes also suggest a range of protein-induced bend angles rather than a fixed geometry [42].…”
Section: Hmgb Mechanismsmentioning
confidence: 99%
“…Structures of HMGB/DNA complexes suggest that induced flexibility would likely be anisotropic [14;16]. HMGB proteins share some features with bacterial IHF [43] and X-ray structures of complexes of the similar HU protein with DNA suggest that a range of induced DNA bend angles are possible [44]. Results from atomic force microscopy for DNA/ HU complexes also suggest a range of protein-induced bend angles rather than a fixed geometry [42].…”
Section: Hmgb Mechanismsmentioning
confidence: 99%
“…IHF bends DNA by 1608 [Rice et al, 1996;Lorenz et al, 1999], and this ability to induce topological changes might be relevant for nucleoid organization. In fact, a single-molecule study demonstrated that binding of IHF to multiple sites could condense linear DNA into a more compact, but randomly coiled structure [Ali et al, 2001].…”
Section: Mechansims Of Nucleoid Organizationmentioning
confidence: 99%
“…A dramatic distortion of the canonical double-helix structure is observed in several DNAprotein complexes that bend DNA, sometimes by nearly 160°o ver a few helical turns (3)(4)(5)(6)(7)(8). The energetic costs of DNA bending on such short lengths is compensated by very specific interactions between protein and DNA that lower the free energy of the complex.…”
mentioning
confidence: 99%